Optimasi peningkatan kualitas air sumur gali melalui penggunaan tawas (Aluminium Potassium Sulfate) terhadap Escherichia coli - Zuriani Rizki; Hastuti Syahnita; Mutia Ulfa Rahmad (Politeknik Kesehatan Kemenkes Aceh, 2021)
Background: well water provide water that comes from a layer of soil that is relatively close to the ground surface, therefore it is easily exposed to contamination through seepage. In general, seepage comes from human excreta, latrines or latrines and animals, as well as from well waste itself, either because the floor or the sewerage are not impermeable to water. The condition of construction and the way the well water is drawn can also be a source of contamination, for example wells with open construction and drawing water with a bucket. One of the fecal contamination bacteria found in well water is Escherichia coli. Alum (Aluminum sulfate) is one of anti-microbial.Objective: To determine the effect of alum with concentrations of 5%, 10% and 15% on the amount of Escherichia coli in well waterMethod: explanatory research (explanatory research) which is to explain the relationship between variables through comparison and hypothesis testing, using a quasi experimental design method with the experimental design used in this study is Completely Randomized Design with 3 repetitions.Results: The results of the ANOVA test on the content of E. coli with various concentrations obtained a P value of 0.000 an alpha value of 0.05, indicating that there was a significant difference in the observed concentrations.Conclusion: Alum with concentrations of 5%, 10% and 15% affected the number of Escherichia coli in well water. The higher the concentration of alum, the better in inhibiting the growth of E.coli bacteria in well water.Conclusion: Alum with concentrations of 5%, 10% and 15% affected the number of Escherichia coli in well water. The higher the concentration of alum, the better in inhibiting the growth of E.coli bacteria in well water.